PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 017 BAGAN PUNAK KECAMATAN BANGKO - HARTATI, YAYUK; Noviana, Eddy; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this study is the low result of learning science subjects. Of the 25 students, only 36.00% or 9 students who complete study results, in addition to the average value of students was 54.60. The low learning outcomes of students in science subjects in class V is caused by: (1) the teacher is not connecting with real life learning materials, so that students find it difficult to understand the material; (2) learning is still centered on the teacher, so the less provides the opportunity for students to interact; (3) students tend to not give the response of the stimulus provided by the teacher; (4) lack of motivation to learn, it can be seen from the students' response to the ongoing learning process; and (5) the teacher is less varied in designing the learning model making it less attractive and to enable students and monotonous. Based on this the researchers conducted a study class action by applying the learning model based problem. This study was conducted in SD Negeri 017 Bagan Punak Kecamatan Bangko, with research subjects fifth grade students with the enrollment of 25 students, with details of 12 male students and 13 female students. The study states that the implementation of inquiry learning model can increase the activity of teachers and students and learning outcomes IPA. This is evidenced by: (1) the activity of the teachers at the meeting I cycle I obtained a score of 22 (50.00%) at the second meeting of the first cycle increased with a score of 27 (61.36%). At the first meeting of the second cycle increased with a score of 34 (77.27%), and at the second meeting of the second cycle increased by a score of 39 (88.64%). Additionally the activity of students has increased at a meeting I cycle I obtained a score of 21 (47.73%), at the second meeting of the first cycle increased by a score of 25 (56.82%). At the first meeting of the second cycle increased by a score of 35 (79.55%) and in the second meeting of the second cycle increased by a score of 37 (84.09%); and (2) improving student learning outcomes characterized of 9 people on base score to 16 people on a daily test I and rose to 21 people on a daily tests II. This means that class into the sample has been completed in the classical style. An increase in the average learning outcomes of the basic score is 36.00 into 64.00 in the first cycle and 84.00 in the second cycle.